Chemical pressure enlarged camouflage color zone in Mn(IV)-activated yellow-green pigments. (September 2022) - Zhou, X.; Zhao, M.-H.; Yang, J.; Han, Y.; Cao, L.; Han, Y.-Y.; Wang, J.; Wang, Y.; Li, M.-R.
Abstract: Environment-friendly and cost-effective versatile yellow-green inorganic pigments are technically significant for natural camouflage but rare. Here, we adopt site-selective parent-doping of Mn–Li into the octahedral Ca-site (Ca B ) of Ca3 TeO6 to deliver vivid greenish pigments by the unprecedented yellow-green Mn 4+ O6 chromophore, yielding tunable pigments resemble to seasonal leaves. The camouflage color zone of these pigments are remarkably enlarged by chemical pressure via Mg 2+ /Sr 2+ -substitution for the A -site Ca (Ca A ). The locally anisotropic and positive chemical pressure on chromophore group is scaled to be around +14.4/+23.3 GPa, as estimated from the accompanied geometric evolution of Mn 4+ O6 . The achieved pigments also demonstrate excellent chemical and thermodynamic stability and high (60–80%) near infrared reflectivity in 1500–2500 nm, showing potential applications for natural camouflage and yellow-green "cool pigments". These findings built a bridge between chemical and equivalently physical pressure, and nominated a way to estimate the overall and local strain/pressure by optical descriptor. Graphical abstract: Greenish Mn 4+ O6 chromophore was observed for the first time by site-selective Mn–Li co-doping in Ca3 TeO6, yielding yellow-green pigments for natural camouflage. The color zone can be further enlarged via locally anisotropic and positive chemical pressure for applications in jungle camouflage and "cool pigments". The local strain-coloration diagram builds a bridge to rate the chemical-physical pressure by optical descriptor. Image 1 Highlights: Octahedral yellow-green chromophore Mn 4+ O6 for the first time discovered in Ca3 TeO6 . These pigments exhibit chemical-pressure enlarged color zone for potential applications in natural camouflage and "cool pigment". The evolution of chromophore senses the local chemical pressure and builds a bridge between chemical and physical pressures.